2021
DOI: 10.3389/feart.2020.605703
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of the Principal Components of the Summertime Ozone Valley in the Upper Troposphere and Lower Stratosphere

Abstract: The key factors affecting the variation of the ‘ozone valley’, which appears during the boreal summer in the upper troposphere and lower stratosphere (UTLS) over the South Asian High (SAH) and its adjacent areas, have not been determined. This study has performed statistical analysis to improve the understanding of the roles of the sea surface temperature (SST), tropopause height, and the West Pacific Subtropical High (WPSH) on the ozone valley. Based on the European Center for Medium-Range Weather Forecasts I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Some disturbances not corresponding to the positions of the relatively-low N 2 values or relatively-high wind shear can also be seen in Figure 10. Wei et al (2016) and Chang et al (2021) have confirmed that the eddy ozone flux is also crucial for the ozone distribution (Weiet al, 2016;Chang et al, 2021). The search for other factors affecting ozone perturbations will thus be a major part of subsequent research.…”
Section: Resultsmentioning
confidence: 96%
“…Some disturbances not corresponding to the positions of the relatively-low N 2 values or relatively-high wind shear can also be seen in Figure 10. Wei et al (2016) and Chang et al (2021) have confirmed that the eddy ozone flux is also crucial for the ozone distribution (Weiet al, 2016;Chang et al, 2021). The search for other factors affecting ozone perturbations will thus be a major part of subsequent research.…”
Section: Resultsmentioning
confidence: 96%
“…In this study, the ozone mass mixing ratio of 300-50 hPa in the UTLS region is used to calculate TCO [53]:…”
Section: Tco* Calculation For the Ozone Valleymentioning
confidence: 99%